Worlds of Difference: European Discourses of Toleration C. 1100-C. 1550 by Cary J. Nederman (University Park: The Pennsylvania State University Press, 2000. 157 pages.) (American Journal of Islam and Society, 2003)
This is an appealing and clearly written account of how European thinkersfrom late medieval to early modern times reflected upon and explored thequestion of what to do about people of different religions and cultures. Inother words, how should their divergent opinions be understood and, eventually,what practical dispositions should be taken toward them? CaryNederman devotes the introduction and first chapter to an excellent,detailed explanation of the book’s focus and goals. Simply put, he is intentupon challenging two currently dominant views: that toleration emerged inEurope only at the time of the Reformation, and that it is ineluctably linkedwith the kind of political liberalism usually associated with John Locke. Tothis end, he calls the reader’s attention to expressions of religious, and evensomewhat political, toleration that appear early in the twelfth century andcontinue well into the sixteenth century. Unfortunately, he does not succeedin this ambitious, even appealing, stratagem as fully as he would havewished, for he admits in passing that he is content to “offer illustrations,”instead of a “comprehensive account,” of this phenomenon ...